De gallo peregrino, the wandering cock - Serge Bahuchet (Revue d'ethnoécologie)
This paper considers the conditions and consequences of the discovery of the turkey Meleagris gallopavo L. (Phasianideae). I try to define how this new animal will be inserted into the European languages, through terminology, into the scientific knowledge, and into uses and practices, planning to specify steps of its acceptance into the European food corpus. For this inquiry, I analyze chronologically successive written evidences, i. e. archives discovered by historians, as well as books (about cooking, agriculture) and dictionaries, in order to underline the steps of the adoption of the turkey in our European civilization (Spain, Italy, France and England).